Effects of climate warming on plant autotoxicity in forest evolution: a case simulation analysis for Picea schrenkiana regeneration. Issue 16 (23rd July 2016) - Ruan, Xiao; Pan, Cun‐De; Liu, Run; Li, Zhao‐Hui; LI, Shu‐Ling; Jiang, De‐An; Zhang, Jing‐Chi; Wang, Geoff; Zhao, Yin‐Xian; Wang, Qiang
Abstract: In order to explore how plant autotoxicity changes with climate warming, the autotoxicity of P. schrenkiana needles' water extract, organic extract fractions, and key allelochemical DHAP was systemically investigated at the temperature rising 2 and 4°C based on the data‐monitored soil temperature during the last decade in the stage of Schrenk spruce regeneration (seed germination and seedling growth). The results showed that the criterion day and night temperatures were 12°C and 4°C for seed germination, and 14°C and 6°C for seedling growth, respectively. In the presence of water extract, the temperature rise of 2°C significantly inhibited the germination vigor and rate of P. Schrenkiana seed, and a temperature rise of 4°C significantly increased the inhibition to the seedling growth ( P < 0.05). Among the three organic fractions, the low‐polar fraction showed to be more phytotoxic than the other two fractions, causing significant inhibitory effects on the seed germination and growth even at low concentration of 0.1 mg/mL, and the inhibition effect was enhanced as temperature increased. The temperature rise significantly enhanced the promotion effect of DHAP, while the inhibition effect of temperature rise became less important with increasing concentration of DHAP. This investigation revealed that autotoxicity of P. schrenkiana was affected by the climate warming. As expected, it provided an insight into the mechanism and effectiveness of allelopathy in bridging the causal relationship between forest evolution and climate warming. Abstract : This work conducted a case study on regeneration of Picea schrenkiana to address how does climate warming affect autotoxicity of plants and then the forest evolution.